Chironomus rishii sp. n., an enigmatic non-biting midge (Diptera: Chironomidae: Chironominae) from Neotropical region - Trivinho-Strixino, Susana; Da Silva, Fabio Laurindo (Zootaxa, 2018)
A new species of Chironomus Meigen, C. rishii (Diptera: Chironomidae: Chironominae) from Brazil, is described and figured as adults male and female, pupa and larva. Adults of C. rishii sp. n. can be recognized by the prominent scutal tubercle and the hypopygium with narrow, elongated and strongly hooked superior volsella. Pupae of this new species are indistinguishable from most of the described Neotropical species, while larvae may be separated by the mentum with deeply incised trifid median tooth and 7 pairs of lateral teeth and the absence of lateral and ventral tubules. This last feature would place C. rishii sp. n. within the 'salinarius group'. However, this is not a group in the systematic sense, but an artificial grouping equivalent to a morphotype that reflects only the tubule character state. It is suggested that the absence of tubules is an adaptation for tolerating a wide range of salinity levels, however the 'salinarius group' had been also recorded in freshwater environments. Here, larvae without abdominal tubules were found in an environment with low levels of salinity, which indicates that the tubule condition may be result of further abiotic pressures, and configures a rather enigmatic scenario to this feature, particularly when considered the fact that larvae of Chironomus having tubules had also been recorded at the same habitat, living under similar conditions of C. rishi sp. n.